Perancangan Peningkatan Kualitas Jasa Usaha Kecil dan Menengah (UMKM) Fotografi - Nabhani, Irfan; Ahmad Dzulfikar, Bilal; Aulawi, Hilmi (Jurnal Kalibrasi, 2024)
The research is aimed at improving the quality of services at UMKM in the photography industry. The creative industries, including the photography subsector, have experienced rapid growth in Indonesia. Therefore, it is important to improve the quality of services in this industry increasing competitiveness and customer satisfaction. The research uses the Quality Function Deployment and Service Quality methods to analyze and understand customer needs, QFD is used as a tool to identify attributes that need to be improved and prioritize improvement. Service Quality is used to measure the gap between expectations and performance in delivering services to customers. The level of customer satisfaction with the quality of X Photgraphy's service has not yet been met, as evidenced by the content of the questionnaire replies distributed to respondents using the Servqual method. Three attributes of service quality that need to be prioritized in order to make improvements based on the classification results are as follows: timely completion of photo results, employees dealing with customer questions and requests in a friendly and clear manner, and comfortable, safe and attractive premises. Action to improve service quality based on the need to minimize dissatisfaction with improvement priority attributes by making improvements including changing company management rules, reducing over orders, adding employees for specific positions, improving the implementation of sops, and adding concepts.